Higher Education Governance in the Arab World Exploring the Challenges of the Education Sector and Social Realities (Springer International Publishing, 2018)
This book offers an insight into the complications higher education is currently facing in the Arab world. It discusses whether governance in international higher education is of particular importance in Arab countries when considering their difference in political systems, cultures, interests, concerns and numerous conflicts. Arab society needs more than ever to strengthen its higher education governance in order to meet current challenges and demands. Higher Education Governance in the Arab World includes insights from the real world and is written by international professionals with the aim of providing a spark of hope for a better future with a clearer understanding on how to move forward.